2020
DOI: 10.1093/nutrit/nuaa118
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and depression risk in older adults: systematic review and meta-analysis

Abstract: Context Diet may be one of the modifiable environmental factors that could reduce depressive symptoms or abate the development of depression without side effects. However, previous reviews mainly focused on general adult populations. Objective The aim of this systematic review and meta-analysis was to explore the association between healthy dietary patterns and depression risk in older adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 71 publications
2
21
1
Order By: Relevance
“…Future studies should include a more accurate and comprehensive dietary assessment to determine the role of diet in depression development (12,64) . For example, high-fat diets are known to cause gut dysbiosis and induce metabolic endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should include a more accurate and comprehensive dietary assessment to determine the role of diet in depression development (12,64) . For example, high-fat diets are known to cause gut dysbiosis and induce metabolic endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent systematic review has demonstrated that adherence to a Mediterranean diet is associated with improvement in mental health (11) . Thus, a healthy dietary pattern could contribute to reducing the risk for depression, and supporting medical treatment of depression, partially decreasing undesirable side effects (12) . Nonetheless, studies linking dietary patterns and depression risk are heterogeneous, and findings remain inconclusive (13) with no studies in some regions such as Latin America (14) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several systematic reviews found conflicting findings across age groups from observational evidence [20][21][22][23][24]. A differential effect of fruit and vegetables was reported in studies that examined the effects of fruit and vegetables separately on depression symptoms [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Today, nutritional support as supplements or dietary interventions characterize adjuvant therapy against depression, anxiety, stress, and cognitive decline [12][13][14][15][16]. Moreover, a great deal of studies have been conducted relating dietary variables and the prevention of mental health disorders [17][18][19]. Together with the aforementioned mechanisms, current evidence suggests that the rich innervation of the gastrointestinal system might deliver impulses and signals to the brain in addition to receiving them [20].…”
mentioning
confidence: 99%